Gastroduodenal safety of Nimesulid (Nimesil, Berlin Chemie) in rheumatic patients with history of ulcer - A. E. Karateyev; D E Karateyev; E L Nassonov (Научно-практическая ревматология, 2003)
Objective. To assess safety of nimesulid in rheumatic pts with history of ulcer or multiple erosions (ME) of stomach and/or duodenal mucosa. Methods. 42 pts with rheumatic diseases aged 22-73 years were included. AH had gastric or duodenal ulcers or ME (n>10) connected with NSAID treatment and confirmed by endoscopy no more than 6 months before the beginning of the study. Pts were included after healing of ulcers and erosions. The pts were randomized to receive Nimesulid 200 mg/day (group 1) or Diclofenac suppositoria 100 mg/day + ranitidine 150 mg/day (group 2). Esophagogastroduodenoscopy was performed before and 12 weeks after the beginning of treatment. Results. Relapse of stomach ulcer was observed in I pts of group 1 (5,6%). Relapse of NSAID-induced ulcers and ME was noted in 6 pts of group 2 (33,3%): in 4 cases stomach ulcers, in 1 case stomach ME, in 1 case duodenal ulcer (p=0,0424). Presence of gastralgias and dyspepsia was noted in 36,8% pts of group 1 and in 20% pts of group 2 (p=0,0539). In 1 pts of group 2 gastralgias were the reason for premature endoscopy. Conclusion. Nimesil (Nimesulid) can be considered as a more safe drug than classical NSAIDs with smaller risk of serious gastroduodenal complications development in rheumatic pts with ulcer history. The results of the study allow to recommend Nimesulid as a drug of choice for treatment of pts with history of NSAID-induced gastropathy.